Rubbercrete mixture optimization using response surface methodology - Mohammed, B.S. (Elsevier Ltd, 2018)
Rubbercrete is made of partially replacing fine aggregate, in normal concrete, with crumb rubber (CR) from scrap tires. Despite several advantages of rubbercrete, one of the most hindering factors on using it in the construction industry is the absence of specific mix design to optimize the mix ingredients. Response surface methodology (RSM) optimization has been incorporated using the design expert to eliminate the difficulty in obtaining the anticipated results. Experimental data of 45 rubbercrete mixtures (from the previous study) have been utilized to develop ANOVA models. These models have also been validated to predict the properties of rubbercrete based on different percentages of CR content and w/c. All models are significant with Prob > F is less than 0.05, and the difference between predicted R-squared and adjustable R-squared is less than 0.2. Also, an experimental validation has been performed for three of the optimized mixtures, and the results have been compared, and the variation in the results have found to be less than 5. It has been concluded that the optimization can be performed for any target strength with desirability as approximately one by improving the performance, reliability for the product and processes. Â© 2017 Elsevier Ltd